Exposure to mercury from dental amalgam: actual contribution for risk assessment - Tuček, Milan; Bušová, Milena; Čejchanová, Mája; Schlenker, Anna; Kapitán, Martin (Central European Journal of Public Health, 2020)
OBJECTIVE: Mercury dental amalgam restorations are an important source of chronic exposure to mercury in the whole population and special attention should be paid not only to occupational exposure to mercury during the preparation and administration of amalgam. The authors' report is an up-to-date contribution to the health risk assessment of mercury use in dentistry, namely occupational exposure to mercury in dentists working with dental amalgam and exposure to mercury in persons treated with amalgam dental restorations. METHODS: Determination of total mercury in samples of biological material (urine, hair) was performed during 2017 and 2018 in 50 persons by the AAS method using the mercury vapour generation technique at 254.6 nm. RESULTS: Current dental exposures based on the most recent findings do not exceed acceptable risk levels and are below the biological limit of mercury in urine valid for occupationally exposed persons (100 μg.g-1 of creatinine), namely median value was 1.48 (min. < limit of detection (LOD), max. 17.14) μg.g-1 of creatinine (40 persons), total mercury content in hair of dental personnel expressed as median value was 0.340 (min. 0.060, max.1.628) μg.g-1. In controls (10 persons) was total mercury content in urine expressed as median value 0.36 (min. < LOD, max. 2.74) μg.g-1 of creatinine, in hair was median value 0.224 (min. 0.059, max. 0.453) μg.g-1. CONCLUSIONS: Authors support opinion that amalgam fillings in the oral cavity are a permanent source of mercury for the body itself.
Keywords: Mercury; vlasy, chlupy; hodnocení rizik; Occupational Exposure; vystavení vlivu životního prostředí; lidé; pracovní expozice; Environmental Exposure; Humans; zubní amalgam; rtuť; Risk Assessment; Hair; Dental Amalgam